Using Digital Games in Technology Oriented STEM Education: The Examination of the Students’ Game Designs - Ismail Donmez; Murat Tekce; Serihan Kirmit (Journal of Education in Science, Environment and Health)
The purpose of this research is to examine the contents of the representations that students used while producing digital games in the scope of STEM education. The descriptive survey model among the other quantitative research methods has been used. Within the scope of this purpose, 300 games from the competition arranged throughout Turkey with the name of ‘’I encode my game’’ have been examined in terms of different variables. Checklists were created by the researchers to analyze the data. In these checklists, mental structures (abstract, concrete, mixed and simple content), the use of violent content, the characters, the subject of the game, the type of points, the dominant colors were examined. Findings show that boys were more interested in the game production process than girls while the counselors were all females. it has been found that students intensively used concrete elements and gave more importance to the educational technologies such as educational-instructional games and quiz shows. Students used human figures, animals, objects and fantasy characters as the protagonists in their games. As for the representation of the human figures, it is seen that the proportions of boys and girls were equal. Digital games in technology-oriented STEM education promote students to join the production process on a large scale. At further researches, it is thought that providing students with educational content like game encoding is highly important.